A Modified Technique in Applying Sponge Soaked with Mitomycin C in Trabeculectomy. Issue 6 (November 2021) - Zhang, Xiulan; Song, Yunhe; Liebmann, Jeffery; Weinreb, Robert N.
Abstract : Abstract: Trabeculectomy with adjunctive use of Mitomycin C (MMC) has been a benchmark for glaucoma filtration surgery for decades. However, there are many variations in the ways that the sponges soaked with MMC are applied during the trabeculectomy surgery. We herein describe our way of placing the MMC-soaked sponges to improve the safety and efficacy of the trabeculectomy. The sponges are placed vertically and posteriorly with the long side of the sponge perpendicular to the limbus, not parallel. This will reduce the size of the conjunctival wound at the limbus to preserve more virgin conjunctiva that can be used for repeated trabeculectomy when needed. This will also facilitate a more posteriorly directed flow of aqueous drainage that, in turn, may increase the success rate of the trabeculectomy. We have obtained encouraging results in our practice, and further large-scale randomized studies seem warranted. Abstract : Supplemental Digital Content is available in the text